Genetic diversity analysis of Cuban traditional rice (Oryza sativa L.) varieties based on microsatellite markers - Álvarez, A.; Fuentes, J.L; Puldon, V; Gómez, P.J.; Mora, L; Duque E., Myriam Cristina; Gallego Sánchez, Gerardo J.; Tohme, Joseph M. (FapUNIFESP, 2007)
Microsatellite polymorphism was studied in a sample of 39 traditional rice (Oryza sativa L.) varieties and 11 improved varieties widely planted in Cuba. The study was aimed at assessing the extent of genetic variation in traditional and improved varieties and to establish their genetic relationship for breeding purposes. Heterozygosity was analyzed at each microsatellite loci and for each genotype using 10 microsatellite primer pairs. Between varieties genetic relationship was estimated. The number of alleles per microsatellite loci was 4 to 8, averaging 6.6 alleles per locus. Higher heterozygosity (H) was found in traditional varieties (HTV = 0.72) than in improved varieties (HIV = 0.42), and 68% of the total microsatellite alleles were found exclusively in the traditional varieties. Genetic diversity, represented by cluster analysis, indicated three different genetic groups based on their origin. Genetic relationship estimates based on the proportion of microsatellite loci with shared alleles indicated that the majority of traditional varieties were poorly related to the improved varieties. We also discuss the more efficient use of the available genetic diversity in future programs involving genetic crosses.